Wading through the swamp: what does tropical peatland restoration mean to national‐level stakeholders in Indonesia?. Issue 4 (30th July 2020) - Ward, Caroline; Stringer, Lindsay C.; Warren‐Thomas, Eleanor; Agus, Fahmuddin; Hamer, Keith; Pettorelli, Nathalie; Hariyadi, Bambang; Hodgson, Jenny; Kartika, Winda D.; Lucey, Jennifer; McClean, Colin; Nurida, Neneng L.; et al.
Abstract : Ecological restoration is considered to play an important role in mitigating climate change, protecting biodiversity, and preventing environmental degradation. Yet, there are often multiple perspectives on what outcomes restoration should be aiming to achieve, and how we should get to that point. In this study we interview a range of policymakers, academics, and non‐governmental organization (NGO) representatives to explore the range of perspectives on the restoration of Indonesia's tropical peatlands—key global ecosystems that have undergone large‐scale degradation. Thematic analysis suggests that participants agreed about the importance of restoration, but had differing opinions on how effective restoration activities to date have been and what a restored peatland landscape should look like. These results exemplify how ecological restoration can mean different things to different people, but also highlight important areas of consensus for moving forward with peatland restoration strategies.